Performance and persistence of phosphate solubilizing Azotobacter chroococcum in wheat rhizosphere - Kumar, V; Aggarwal, N K; Singh, B P (Folia microbiologica, 2000)
Survival and establishment of inoculant strains of Azotobacter chroococcum NV 11 and its mutant NV 43 were assessed in sterilized soil and rhizosphere soil of wheat plants at 7 and 15 d interval, respectively, after sowing, i.e., up to 45 d under pot-house conditions. There was an apparent decrease in population of both strains in bulk soil but a steady increase was observed in root zones of the wheat plant. 10(3) to 10(4) introduced bacteria per g root were found sticking to roots. Further studies indicated that inoculant strains of Azotobacter could survive, proliferate and establish well in root zones.
Keywords: časové faktory; fosfáty; Azotobacter; Triticum; Phosphates; pšenice; kořeny rostlin; Plant Roots; Time Factors; půdní mikrobiologie; Soil Microbiology